The Effect of Tightrope Walker Exercise on the Static Balance of Children Aged 4-7 Years with Flat Foot Conditions at KB Islamic Kindergarten Sultan Agung 2 Semarang City - Fitratun Najizah; Shella Dhika Rahmawati; Cintya Putri Anisah; Sofia Mardiana (International Journal Of Health Science, 2023)
Balance is the ability to maintain the body in the center of mass of the body against a fulcrum to oppose gravity in a position that is influenced by the sensory system, musculoskeletal and external effects. Flat foot is a musculoskeletal disorder in children. At the age of 5-6 years is a period of developing children's motor skills, especially balance, which is very good when stimulated in the form of games. One stimulation to improve the balance of flat foot children aged 4-7 years is tightrope walker training. The aim of this study was to determine the effect of tightrope walker training on the balance of children with flat feet aged 4-7 years. This research is a quasi experiment with a pre and post test design approach, namely the sample in the treatment group was given tightrope walker training for 4 weeks with a frequency of 2 times a week. Balance measurement uses the one legged stance test. Data analysis in this study used statistical tests with a significance level of 0.05 using the sample paired t-test. The results of statistical tests show that there is a significant influence between giving tightrope walker training on the static balance of children with flat foot conditions. The implementation of tightrope walker training for flat foot children is recommended for static balance problems in children. The conclusion of this research can be implemented that tightrope walker training has an influence on the balance of children with flat feet aged 4-7 years.